A review of thermal nondestructive testing methods for aerospace structures in the former USSR; La Recherche Aerospatiale (English Edition); № 6 - Vavilov V. P. Vladimir Platonovich (1991, 1991)
A review is presented of thermal nondestructive testing methods developed in the former USSR, along with several applications dealing with high technology structures and materials commonly utilized in the aerospace industry. The original features and strengths of these studies are highlighted, and some of the weaknesses are pointed out as well. Attention is focused on a better understanding of the subject and to illustrate areas for future cooperation.